In Search of Cognitive Promotive and Protective Factors for Word Reading. (3rd September 2021) - Slomowitz, Rebecca F.; Narayan, Angela J.; Pennington, Bruce F.; Olson, Richard K.; DeFries, John C.; Willcutt, Erik G.; McGrath, Lauren M.
ABSTRACT: This study examined whether strong cognitive skills (i.e. vocabulary, rapid naming, verbal working memory [VWM], and processing speed [PS]) contributed to resilience in single-word reading skills in children at risk for reading difficulties because of low phonological awareness scores (PA). Promotive factors were identified by main effects and protective factors through PA x cognition interactions. This study included 1, 807 children ages 8–16. As predicted, all cognitive skills were significantly related to reading, consistent with promotive effects. A significant, but small effect PA x vocabulary interaction (R 2 change = .002, p = .00038) was detected but its form was not consistent with a classic protective effect. Rather, the PA x vocabulary interaction was consistent with a "skill-enhancement" pattern, such that children with strong PA and vocabulary skills had better than expected reading. This study provides a framework for reading resilience research and directs attention to promotive mechanisms underlying reading success.